Development of a Structural Model of Emotional Divorce Based on the Dark Triad Personality Traits and Conflict Resolution Styles with the Mediation of Marital Conflicts - Sadegh Khani, Marjan; Emamipour, Suzan; Mirhashemi, Malek (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aims to model the structural equations of emotional divorce based on dark personality traits and conflict resolution styles with the mediation of marital conflicts. Methods and Materials: The research method was descriptive-correlational based on structural equations. The statistical population included all married women aged 25-50 years at Islamic Azad University (Yadegar-e-Imam, Abolfatoh Razi (Mothers), and Tehran North campuses) in the first half of 2021, selected online due to the COVID-19 pandemic using convenience sampling. The research instruments included the Emotional Divorce Questionnaire (Gottman, 1994), the Dark Triad Personality Questionnaire (Johnson & Webster, 2010), Rahim’s Conflict Resolution Styles (Rahim, 1983), and the Marital Conflict Questionnaire (Sanaei, 1996). Data were analyzed using SPSS and AMOS software. Findings: The results of structural equation modeling indicated that the proposed model fits the empirical data (RMSEA = 0.063). There was a significant relationship between Machiavellianism and emotional divorce (β = 0.173), and between constructive style (β = -0.556) and non-constructive style (β = 0.26) with marital conflicts. The indirect path coefficient of narcissistic traits (P = 0.007), constructive (P = 0.011) and non-constructive conflict resolution styles (P = 0.005) with the dependent variable emotional divorce through the mediating variable of marital conflicts was significant. However, the mediating role of marital conflicts in the relationship between antisocial traits (P = 0.798) and Machiavellianism (P = 0.877) with emotional divorce was not confirmed. Conclusion: Dark personality traits and constructive conflict resolution styles can indirectly affect emotional divorce by influencing marital conflicts, in addition to their direct effect.